An innovative joint interface design for reducing intermetallic compounds and improving joint strength of thick plate friction stir welded Al/Mg joints - Yang Xu; Liming Ke; Yuqing Mao; Jifeng Sun; Yaxiong Duan; Limin Yu (Journal of Magnesium and Alloys, 2023)
Friction stir welding of dissimilar Al/Mg thick plates still faces severe challenges, such as poor formability, formation of thick intermetallic compounds, and low joint strength. In this work, two joint configurations, namely inclined butt (conventional butt) and serrated interlocking (innovative butt), are proposed for improving weld formation and joint quality. The results show that a continuous and straight intermetallic compound layer appears at the Mg side interface in conventional butt joint, and the maximum average thickness reaches about 60.1 µm. Additionally, the Mg side interface also partially melts, forming a eutectic structure composed of Mg solid solution and Al12Mg17 phase. For the innovative butt joint, the Mg side interface presents the curved interlocking feature, and intermetallic compounds can be reduced to less than 10 µm. The joint strength of innovative butt joint is more than three times that of conventional butt joint. This is due to the interlocking effect and thin intermetallic compounds in the innovative joint.